2008
DOI: 10.1111/j.1439-0531.2008.01248.x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Cryopreservation in Brown Bear (Ursus arctos): Preliminary Aspects

Abstract: The development of sperm cryopreservation procedures in brown bear is the basis for establishing a specific genetic resource bank aimed at the preservation of a Cantabric brown bear population, which is seriously threatened. Several issues complicate the development of these cryopreservation procedures: lack of previous specific studies, a high incidence of urospermia and spermagglutination observed in bear ejaculates. Moreover, the availability of individuals for research from these threatened populations is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 74 publications
1
26
0
Order By: Relevance
“…The present study must be situated in the context of the conservation of the endangered Cantabric brown bear (∼150 individuals restricted to two isolated populations in the north of Spain) and in the development of artificial reproduction techniques to establish germplasm banks to aid in preservation of these populations (Anel et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The present study must be situated in the context of the conservation of the endangered Cantabric brown bear (∼150 individuals restricted to two isolated populations in the north of Spain) and in the development of artificial reproduction techniques to establish germplasm banks to aid in preservation of these populations (Anel et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies on electroejaculation of bears have indicated an elevated incidence of urospermia, with the consequent loss of semen quality (Okano et al 2004;Chen et al 2007;Kojima et al 2001;Anel et al 2008). Thus, we considered that developing a protocol for washing sperm samples was critical for the success of a sperm recovery plan in the brown bear.…”
Section: Discussionmentioning
confidence: 97%
“…Some species such as the bear (Kojima et al 2001;Chen et al 2007;Anel et al 2008) may yield semen contaminated by the urine during electroejaculation. A usual method for counteracting the noxious effect of urine contamination is to add large volumes of extender to the contaminated sample and centrifuge it immediately, removing the supernatant and substituting it with clean medium (Makler et al 1981;Kim and Kim 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, ejaculates often come with urine contamination (e.g. Anel et al, 2008) or they may come with or without the relevant secretions from all accessory glands. In elephants this is manifested by occasional ejaculates with very sticky consistency indicating that high level of secretions from the bulbourethral gland are present (personal observation) whereas in rhinoceros it is manifested by high viscosity of the ejaculate (Behr et al, 2009b).…”
Section: The Malementioning
confidence: 99%